The Distribution of Common Stock Price Changes: An Application of Transactions Time and Subordinated Stochastic Models - Westerfield, Randolph (Journal of Financial and Quantitative Analysis, 1977)
Randolph Westerfield, The Distribution of Common Stock Price Changes: An Application of Transactions Time and Subordinated Stochastic Models, The Journal of Financial and Quantitative Analysis, Vol. 12, No. 5 (Dec., 1977), pp. 743-765